E-Readiness Evaluation of High School Student Biology Learning During the Covid-19 Pandemic - Jamaluddin Jamaluddin; A. Wahab Jufri; Agus Ramdani (Jurnal Penelitian Pendidikan IPA, 2021)
E-Readiness is the level of readiness that a person needs to understand and apply information and communication technology. E-Readiness can also be interpreted as readiness to sort, interpret, and process digital knowledge. E-Readiness is very important for students to be able to take part in online learning during the Covid-19 pandemic. The purpose of this study was to describe the level of E-Readiness in learning biology for high school students in West Lombok Regency in participating in online learning of biology subjects. This study uses a quantitative descriptive research method. The instrument used to obtain student E-Readiness data is the E-Readiness questionnaire. Data collection was carried out using a survey technique by distributing questionnaires using the google form application. The number of respondents who filled out the questionnaire was 622 students. Data analysis was carried out using descriptive statistical analysis techniques that refer to the An Integration Information Rich E-Readiness Assessment Tool evaluation model. Data analysis using the evaluation model was carried out on each indicator of the E-readiness segment. The results of data analysis found that: (1) Enterprise E-Readiness segment 79.88% ready; (2) ICT readiness segment 82.96 ready; (3) Human resources readiness 83.88 ready, 4. Information readiness segment, 70.72% ready, and 5. External environment readiness 84.42% is ready. From the data analysis, it was found that the E-Readiness of studying biology for high school students was 3.1% Very Unprepared, 16.4% Unprepared, 54.9% Ready, and 25.6% Very Ready. On average 80.5% of high school students have good skills in using information and communication technology. Thus, it can be concluded that an average of 80.5% of students' E-Readiness in learning biology had a good level of readiness, and 19.5% did not yet have a readiness level to participate in online biology learning in West Lombok Regency